(untitled) (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, we investigate the superconvergence results for optimal control problems governed by parabolic equations with semi-discrete mixed finite element approximation. We use the lowest order mixed finite element spaces to discrete the state and costate variables while use piecewise constant function to discrete the control variable. Superconvergence estimates for both the state variable and its gradient variable are obtained.